Risk of bias of animal studies on regenerative procedures for periodontal and peri-implant bone defects - a systematic review - Faggion Junior, Clóvis Mariano; Giannakopoulos, Nikolaos Nikitas; Listl, Stefan (Journal of clinical periodontology, 2011)
Objectives (1) To assess the risk of bias of studies in which animal models were used for investigating regenerative therapies for periodontal and peri-implant defects. (2) To investigate changes in risk of bias by comparing samples drawn from two different publication periods. Material & Methods We searched the PubMed and LILACS electronic databases, independently and in duplicate, for randomized and controlled trials published from 1998 to 2000 and from 2008 to 2010. Hand searching included search of 10 dental journals, in the issues published between August 2008 and August 2010. Studies on non-human primates and canines were included. We assessed independently and in triplicate the risk of bias with reference to a six-item checklist based on the Cochrane Collaboration's tool for assessing the risk of bias and information about formal sample size calculation. Results One hundred and seven studies were included in the review. Checklist items were poorly reported in the studies selected, and therefore for most of the studies, the risk of bias was unclear. Conclusion As a result of the unclear risk of bias of animal studies in periodontal and peri-implant treatments, it is difficult to determine the accuracy of treatment effect estimates. There is a need for standardization of reporting procedures on animal experiments.
Gesehen am 02.05.2022